Genetic predictors of cardiovascular morbidity in Bardet–Biedl syndrome. (8th April 2014) - Forsythe, E.; Sparks, K.; Hoskins, B.E.; Bagkeris, E.; McGowan, B.M.; Carroll, P.V.; Huda, M.S.B.; Mujahid, S.; Peters, C.; Barrett, T.; Mohammed, S.; Beales, P.L.
Abstract : Bardet–Biedl syndrome is a rare ciliopathy characterized by retinal dystrophy, obesity, intellectual disability, polydactyly, hypogonadism and renal impairment. Patients are at high risk of cardiovascular disease. Mutations in BBS1 and BBS10 account for more than half of those with molecular confirmation of the diagnosis. To elucidate genotype–phenotype correlations with respect to cardiovascular risk indicators 50 patients with mutations in BBS1 were compared with 19 patients harbouring BBS10 mutations. All patients had truncating, missense or compound missense/truncating mutations. The effect of genotype and mutation type was analysed. C‐reactive protein was higher in those with mutations in BBS10 and homozygous truncating mutations (p = 0.013 and p = 0.002, respectively). Patients with mutations in BBS10 had higher levels of C peptide than those with mutations in BBS1 (p = 0.043). Triglyceride levels were significantly elevated in patients with homozygous truncating mutations (p = 0.048). Gamma glutamyl transferase was higher in patients with homozygous truncating mutations (p = 0.007) and heterozygous missense and truncating mutations (p = 0.002) than those with homozygous missense mutations. The results are compared with clinical cardiovascular risk factors. Patients with missense mutations in BBS1 have lower biochemical cardiovascular disease markers compared with patients with BBS10 and other BBS1 mutations. This could contribute to stratification of the clinical service.